Gender differences in reduced substance P (SP) in children with slow-transit constipation - Yik, Yee Ian; Farmer, Pamela J.; King, Sebastian K.; Chow, C.W.; Hutson, John M.; Southwell, Bridget R. (Springer Verlag, 2011)
Purpose: Adult slow-transit constipation (STC) occurs predominantly in females and is associated with low numbers of substance P (SP)-containing nerves in colonic circular muscle. Aim: To determine if reduced SP nerves is female predominant in paediatric STC. Methods: Children with STC were identified from records of more than 600 nuclear transit studies (NTS) and intestinal biopsies done for intractable chronic constipation between November 1998 and March 2009. Colonic seromuscular biopsies collected from hepatic and splenic flexures, and sigmoid colon were processed for immunohistochemistry. Nerve fibre density in circular muscle containing SP was measured qualitatively by a pathologist. Results: Eighty-eight children with chronic constipation had both NTS and intestinal biopsies. Seventy-eight children (52 M; age 2-15.5 years; mean 7.7 years) had STC diagnosed by NTS. SP was reduced in 10/26 girls, but only 11/52 boys. Conclusion: In this sample, STC was more common in boys than girls. However, in girls with STC, SP deficiency occurred in 40%, when compared with 20% of boys. During puberty, the percentage of girls with reduced SP decreased, whilst the percentage of boys increased. These results suggest that STC is heterogeneous and that there are some gender differences, the implication of which requires further investigation. © 2011 Springer-Verlag.